Ritual Pange Manuk Sebagai Dasar Pendidikan Karakter di Suku Walan - Maria Prisilya Purnamalon; Indar Sabrib; Autar Abdullah (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2023)
Pange Manuk is a community ritual in Manggarai, East Nusa Tenggara Province. The purpose of this ritual is to pray or invoke the ancestral spirits or the universe through an animal intermediary, such as a rooster. The Pange Manuk ritual is held for every experience or event in human life: birth, social life, education, agriculture, health and death. This study aims to analyze the values of character education in the Pange Manuk ritual. The results found through this research indicate that the ritual contains tangible and intangible local wisdom values. In addition, this ritual also contains moral values that should be learned and preserved as a basis for behavior for future generations. This proves that character education taught in schools must start from the family. To preserve this ritual, the education system must be based on local wisdom values. The method used in this study is qualitative by linking ethnographic data. This article can be a source of learning for the community